2023
DOI: 10.3390/vaccines11081304
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation TB Vaccines: Progress, Challenges, and Prospects

Li Zhuang,
Zhaoyang Ye,
Linsheng Li
et al.

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), is a prevalent global infectious disease and a leading cause of mortality worldwide. Currently, the only available vaccine for TB prevention is Bacillus Calmette–Guérin (BCG). However, BCG demonstrates limited efficacy, particularly in adults. Efforts to develop effective TB vaccines have been ongoing for nearly a century. In this review, we have examined the current obstacles in TB vaccine research and emphasized the significance of understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 316 publications
0
28
0
Order By: Relevance
“…The majority of infected individuals exhibit no symptoms and are classified as having LTBI. Without treatment, around 5−10% of LTBI patients will develop TB over their lifetime, emphasizing the importance of treating LTBI to prevent disease progression 9,150,151 . The Guidelines for the Treatment of Latent Tuberculosis Infection: Recommendations from the National Tuberculosis Controllers Association and CDC guide LTBI treatment.…”
Section: Therapeutic Intervention Strategies For Tbmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of infected individuals exhibit no symptoms and are classified as having LTBI. Without treatment, around 5−10% of LTBI patients will develop TB over their lifetime, emphasizing the importance of treating LTBI to prevent disease progression 9,150,151 . The Guidelines for the Treatment of Latent Tuberculosis Infection: Recommendations from the National Tuberculosis Controllers Association and CDC guide LTBI treatment.…”
Section: Therapeutic Intervention Strategies For Tbmentioning
confidence: 99%
“…: (1999) S‐03) and was approved by the China Food and Drug Administration as a vaccine for adjunctive treatment of TB (Approval No. : S20010003) 8,9,241 . Originally produced by Anhui Zhifei Longcom Biologic Pharmacy Co. Ltd. (now Anhui Zhifei Biopharmaceutical Co. Ltd.), Vaccae™ has played an important role in enhancing immunity, promoting phagocytosis, regulating bidirectional immune responses, and reducing pathological damage.…”
Section: Therapeutic Intervention Strategies For Tbmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the current status of anti-tuberculosis vaccine development, previous studies have demonstrated that traditional live attenuated vaccines, such as BCG, exhibit a protective efficacy ranging from 0 to 86% [11]. However, the progress of nucleic acid vaccines, including DNA vaccines, has been hindered since the research boom at the end of the last century, primarily due to the risk of genetic contamination [1].…”
Section: Introductionmentioning
confidence: 99%